2005
DOI: 10.3989/gya.2005.v56.i4.94
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lard oxidation by fractions of different essential oils

Abstract: RESUMENInhibición de la oxidación de la manteca de cerdo por fracciones de diferentes aceites esenciales.Se examinó la capacidad de los aceites esenciales de Origanum vulgare L. spp. hirtum, Thymus vulgaris L., Thymus serpyllum L., Satureja montana L. y Satureja cuneifolia Ten. para inhibir la oxidación de la manteca de cerdo pura. Excepto Satureja cuneifolia Ten., todos los aceites esenciales mostraron un acusado perfil fenólico caracterizado por la presencia de fenoles monoterpéni-cos-timol y carvacrol. El m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 24 publications
3
29
0
1
Order By: Relevance
“…The α-tocopherol, ascorbic acid, BHT, and EO showed the highest inhibition potency, respectively. Our findings (Table 2) revealed that BHT was destroyed at 100°C temprature in agreement with previous studies (Kulisic et al 2005). The method used in this study proved that EO possessed a weak inhibitory effet against the SFO autooxidation process under the conditions (100°C and an airflow rate of 15 L/h).…”
Section: Antioxidant Activitiessupporting
confidence: 92%
“…The α-tocopherol, ascorbic acid, BHT, and EO showed the highest inhibition potency, respectively. Our findings (Table 2) revealed that BHT was destroyed at 100°C temprature in agreement with previous studies (Kulisic et al 2005). The method used in this study proved that EO possessed a weak inhibitory effet against the SFO autooxidation process under the conditions (100°C and an airflow rate of 15 L/h).…”
Section: Antioxidant Activitiessupporting
confidence: 92%
“…En la figura 3 se observa que en la medida en que se aumenta la concentración del antioxidante, aumentan el factor protector que ejerce el antioxidante en la matriz grasa. Kulisic et al (2005), reportaron un factor de inhibición de oxidación de la grasa de cerdo de 2,0; y 1,7 usando como antioxidante aceite esencial de otras plantas aromáticas entre estas Origanum vulgare L y Thymus vulgaris L. respectivamente, sin embargo, a pesar de emplear concentraciones más elevadas y condiciones menos drásticas a las empleadas en esta investigación obtuvieron menores índices de inhibición, lo que pone de manifiesto el elevado potencial antioxidante del extracto de cúrcuma.…”
Section: Fig 2: Influencia Del Grado Alcohólico En La Extracción De unclassified
“…Altundag and Aslim (2011), Baser et al (2001), Yucel et al (2009) , Eminagaoglu et al (2007), Kosar et al (2003Kosar et al ( , 2008, Kulisic et al (2005), Oke et al (2009aOke et al ( , 2009b Alinkina et al (2013), Alizadeh (2011), Alizadeh et al (2010a), Bandoniene et al (2002), Deighton et al (1994), Dikbas et al (2011), , Esquivel et al (1999), Exarchou et al (2002), Gulluce et al (2003), Hosseini et al (2013), Inotai et al (2012), Kalantzakis and Blekas (2006), Kosar et al (2005), Madsen et al (1996Madsen et al ( , 1998, Plander et al (2012), Shojaee-Aliabadi et al (2013), Trojakova et al (2001), and Yesiloglu et al (2013) …”
Section: S Wiedemannianamentioning
confidence: 99%